2019
DOI: 10.1016/j.ijid.2019.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis seronegativity in pregnant women in the city of Al Ain, United Arab Emirates

Abstract: As the current recommendation of administering Tdap (tetanus-diphtheria-acellular pertussis) to all pregnant women has not been widely implemented in the United Arab Emirates (UAE), we aimed to ascertain the prevalence of pertussis seronegativity during pregnancy. Methods: IgG antibodies against Bordetella pertussis toxin (PT) were measured in 213 women attending the antenatal clinic at Oasis hospital, Al Ain, UAE. Results were compared by maternal age, nationality and gestational age with the Kruskal-Wallis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Hence, the effects of poor adult vaccine uptake rates have been masked by a young population, though not for long. As for vaccination studies, those are not extensive and deal with either specific vaccines or specific age groups; however, their results still show a lack of vaccine uptake and a high level of disease susceptibility (13)(14)(15). The UAE's national agenda specifies a wide-ranging work program centered around six national priorities, the fourth of which is a "world-class healthcare" (28).…”
Section: Discussion Adult Vaccination: the Global And Local Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the effects of poor adult vaccine uptake rates have been masked by a young population, though not for long. As for vaccination studies, those are not extensive and deal with either specific vaccines or specific age groups; however, their results still show a lack of vaccine uptake and a high level of disease susceptibility (13)(14)(15). The UAE's national agenda specifies a wide-ranging work program centered around six national priorities, the fourth of which is a "world-class healthcare" (28).…”
Section: Discussion Adult Vaccination: the Global And Local Landscapementioning
confidence: 99%
“…Yet very few studies have looked at this in the Middle East and North Africa (MENA) region and even less locally. In the United Arab Emirates (UAE), vaccination has been an under-researched topic with only a few studies exploring specific vaccines, such as influenza or Human Papilloma Virus (HPV) (13)(14)(15). However, no studies have looked at physicians and their role in promoting general adult vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Although contact with mild or asymptomatic pertussis cases in the society may provide protective antibodies against the disease, a significant part of the society remains susceptible to the disease in adulthood as corroborated with the data presented in the previous section. [25][26][27] Studies showing immunity against pertussis in pregnant women are extremely limited in Turkey. In the study conducted by Ercan et al 19 72% of pregnant women were found to be immune to pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in other countries, the rates of immunity in pregnant women vary between 25% and 97.1%. 15,16,27 It is thought that this difference can be attributed to the differences in the vaccination programs, different probability of the prevalence of pertussis disease and differences in disease prevelance rates of different countries. 3,[12][13][14]16,17 Pertussis is usually diagnosed serologically or clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, PT-IgG was undetectable in 75% of pregnant women attending antenatal clinic at the Oasis hospital, Al Ain, UAE. PT-IgG geometric mean did not differ among women of different age groups [ 49 ].…”
Section: Efficacy and Effectivenessmentioning
confidence: 99%